The theory of externalities, public goods, and club goods - Cornes, Richard 1946- (Cambridge University Press, 1996)
This book presents a theoretical treatment of externalities (i.e. uncompensated interdependencies), public goods, and club goods. The new edition updates and expands the discussion of externalities and their implications, coverage of asymmetric information, underlying game-theoretic formulations, and intuitive and graphical presentations. Aimed at well-prepared undergraduates and graduate students making a serious foray into this branch of economics, the analysis should also interest professional economists wishing to survey recent advances in the field. No other single source for the range of materials explored is currently available. Topics investigated include Nash equilibrium, Lindahl equilibria, club theory, preference-revelation mechanism, Pigouvian taxes, the commons, Coase Theorem, and static and repeated games. The authors use mathematical techniques only as much as necessary to pursue the economic argument. They develop key principles of public economics that are useful for subfields such as public choice, labor economics, economic growth, international economics, environmental and natural resource economics, and industrial organization